PENERAPAN PBL DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI SISWA SMAN 1 BATUKLIANG-LOMBOK TENGAH - Burhan Burhan; Lalu M Istiqlal; Zulkarnain Zulkarnain (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
This study aims to improve the learning outcomes of Sociology through the application of problem-based learning models at SMAN 1 Batukliang, Central Lombok. This type of research is included in the category of Classroom Action Research, which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class XI IPS 1. Data were collected using observation, interview, and documentation techniques. Based on the results of data analysis, it is known that the increase in learning outcomes in the cognitive domain from cycle I to cycle II was 11,76%. The increase in learning outcomes in the affective domain from cycle I to cycle II was 18,30%. The increase in learning outcomes in the psychomotor domain was 19,72%. The increase in classical completeness according to KKM reached 89,7%. In addition, the average class managed to achieve the target success indicator, which was 65, with an average result of 81,04. Changes in student behavior in cycles I and II also prove that the application of this model can significantly improve student learning outcomes. The results of this study indicate that by implementing a problem-based learning model, the learning outcomes of Sociology students of class XI IPS 1 SMA Negeri 1 Batukliang in the 2023/2024 Academic Year can be improved.